Teori Belajar Behavioristik Dan Penerapannya Dalam Pembelajaran Siswa Sekolah Dasar (International Forum of Researchers and Lecturers, 2024)
This research was created to discuss further how educators provide appropriate stimuli so that the learning process of elementary school students can run more effectively according to behavioristic learning theory. This article aims to find out and explain behavioristic learning theory, its characteristics and application in learning, especially for elementary school students. This article uses literature studies to search for and find answers to problems through data from library reviews from various sources and media, both books and e-journals. The results show that behavioristic theory plays a very important role in the learning process in which it is applied, educators are required to design learning and provide appropriate stimuli which will then be responded to actively by students in the learning process in order to realize effective, structured learning and establish interaction and discussion of information.